Impact of an Advanced Pharmacy Practice Experience Student-Run "Meds 2 Beds" and Discharge Counseling Program on Quality of Care. (October 2019) - Conliffe, Brette; VanOpdorp, Jocelyn; Weant, Kyle; VanArsdale, Vanessa; Wiedmar, Jennifer; Morgan, Jessie
Purpose: As health care progresses toward pay for performance reimbursement models and focus is placed on the patient as a consumer, health care systems must adapt by initiating new programs and services. This institution responded by implementing a "Meds 2 Beds" program integrating clinical services with dispensing and medication delivery during transitions of care. This study evaluates outcomes relevant to patients, health care providers, pharmacists, and administrators.Methods: This observational chart review evaluated the effectiveness of a "Meds 2 Beds" program from May 1, 2014, through December 1, 2015. Patients who participated in this program were matched 1:1 with controls who did not. The primary outcome was 30-day hospital readmission. Secondary outcomes included 30-day emergency department (ED) visits, patient satisfaction, and financial impact.Results: In this sample, 185 "Meds 2 Beds" patients were matched to 185 controls. Thirty day readmission occurred in 16 (8.7%) "Meds 2 Beds" cases and 19 (10.3%) controls ( P = .71). Rates of 30-day ED visits were nonsignificantly reduced in cases (22 [11.9%] vs 33 [18.1%]; odds ratio = 0.62, P = .11) and occurred significantly later (11 vs 7 days, P = .03).Conclusions: This study showcases a creative medication delivery and discharge counseling program. The program provides financial benefit to the institution creating a direct revenue stream from prescription dispensing while highlighting a potential for reduced readmissions and ED visits (although a statistically significant difference was not demonstrated in this analysis). A similar model can be adopted by other health care institutions to improve the quality of patient care.